1987
DOI: 10.1515/cclm.1987.25.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Aminolaevulinate Dehydratase Porphyria in Infancy. A Clinical and Biochemical Study

Abstract: Summary: Homozygous deficiency of aminolaevulinate dehydratase (porphobilinogen synthase, EC 4.2.1.24) was diagnosed in a small child. The clinical presentation was unique since severe Symptoms were already present in the neonatal period. The patient, a boy, now three-years old, had recurrent attacks of pain, vomiting, hyponatraemia and Symptoms of polyneuropathy engaging motor functions including respiration. The clinical course of the disease from birth on is related, äs are the results of various attempts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 24 publications
(25 reference statements)
1
34
1
Order By: Relevance
“…ALAD purified from various mammalian sources, including humans (30), is known to be a homo-octamer, comprising 8 identical subunits of 36,000 (1). It is interesting to specu- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…ALAD purified from various mammalian sources, including humans (30), is known to be a homo-octamer, comprising 8 identical subunits of 36,000 (1). It is interesting to specu- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…AIP is a dominant porphyria due to half-normal levels of the third enzyme in the heme biosynthesis pathway. Furthermore, affected individuals with the recessive ALAD-deficient porphyria manifest chronic neurologic manifestations (20)(21)(22). Finally, asymptomatic heterozygotes for the latter porphyria develop acute lead poisoning when exposed to low levels of lead (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…These results were not due to differences in water intake or anemia. This possibility was a concern since it has been shown that a low blood iron status can increase lead absorption; conversely, it has also been proposed that lead can cause anemia (Eisinger, 1978;Schifman et al, 1982;Thunell et al, 1987). In our experiments, intake of water containing lead and hematocrit measures did not show significant differences among the animals in any of our exposure protocols and thus did not produce an anemic state in the animals.…”
Section: Discussionmentioning
confidence: 55%